A method for increasing the melt strength of degradable plastics
By adding melt reinforcement and catalyst with active functional groups to the bio-based degradable plastic, and using graphyne as a support to blend extrusion process, the problem of low melt strength of the bio-based degradable plastic is solved, and its melt strength and thermoformability are significantly improved.
Patent Information
- Application Number
- CN202211301304.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-24
AI Technical Summary
The low melt strength of bio-based degradable plastics leads to poor thermoforming and poor processing performance.
By blending and extruding the matrix with a melt reinforcement and catalyst with active functional groups, graphyne is used as a support to increase the number of long branched chains of the matrix material, thereby improving melt strength and thermoformability.
The melt strength and thermoformability of bio-based degradable plastics are significantly improved, and their processing properties are improved.
Smart Images

Figure BDA0003904832510000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of modification of degradable plastics, and in particular to a method for increasing the melt strength of degradable plastics. Background Art
[0002] Degradable plastics refer to a type of plastic whose products have various properties that meet the requirements of use, maintain their properties during the shelf life, and can be degraded into environmentally friendly substances under natural environmental conditions after use. There are many types of degradable plastics, including photodegradable plastics, biodegradable plastics, photo / oxidation / biodegradable plastics, carbon dioxide-based biodegradable plastics, thermoplastic starch resin degradable plastics, etc.
[0003] Bio-based degradable materials are currently one of the most effective ways to solve white pollution. However, most bio-based degradable plastics have few long branches in the molecular chain, extremely low melt strength, insufficient strain hardening, are hard and brittle in thermoforming, and have a very narrow processing temperature range and poor thermoforming properties. For example, bio-based degradable plastics such as polylactic acid are very difficult to foam due to their low melt strength, and it is difficult to obtain high-multiplier foamed products. Therefore, how to improve their melt strength is one of the research hotspots in this industry. Summary of the invention
[0004] In order to solve the problem of low melt strength of bio-based degradable plastics mentioned in the background technology, the present invention provides a method for enhancing the melt strength of degradable plastics, which is applied to bio-based degradable plastics such as polylactic acid to greatly improve the melt strength and thermoformability.
[0005] The specific plan is:
[0006] A method for enhancing the melt strength of a degradable plastic comprises the steps of: mixing a matrix, a melt enhancer with an active functional group and a catalyst, adding the mixture into a twin-screw extruder, and performing reaction extrusion to obtain the degradable plastic.
[0007] When implementing the above embodiment, preferably, the melt enhancer with active functional groups is obtained by grafting a monomer with active functional groups onto graphyne and copolymerizing it with a comonomer.
[0008] When implementing the above embodiment, preferably, the monomer with active functional group is one or more of acrylic acid, maleic anhydride, methacrylic acid or glycidyl methacrylate.
[0009] When implementing the above embodiment, preferably, the comonomer is one or more of methyl methacrylate, butyl methacrylate or butyl acrylate.
[0010] When implementing the above embodiment, preferably, the preparation steps of the melt enhancer with active functional groups include:
[0011] Step 1: preparing a monomer solution with an active functional group at a concentration of 1 to 5 mol / L, adding graphyne to the monomer solution with an active functional group at a ratio of 1 to 3 g / L, and stirring to obtain a mixed liquid;
[0012] Step 2: irradiating the mixed liquid obtained in step 1 with γ-rays, and obtaining the grafted graphyne with active functional group monomer after drying;
[0013] Step 3: adding the active functional group-grafted graphyne monomer obtained in step 2 and the comonomer to an aqueous solution of sodium dodecyl sulfate, mixing and stirring, and pre-emulsifying to obtain a pre-emulsified monomer;
[0014] Step 4: heating the sodium dodecyl sulfate aqueous solution to 40°C-80°C at a stirring speed of 100-300 r / min, and dropping the pre-emulsified monomer obtained in step 3 into the sodium dodecyl sulfate aqueous solution for 2-6 hours. After the dropwise addition is completed, adding ammonium persulfate and sodium bisulfite in 3 batches, controlling the reaction temperature at 40°C-80°C, and reacting for 10-20 hours to obtain a polymer emulsion;
[0015] Step 5: Drying the polymer emulsion to obtain a melt intensifier with active functional groups.
[0016] When implementing the above embodiment, preferably, in step 2, the irradiation dose is 50 to 500 kGy, and the irradiation dose rate is 10 to 200 kGy / h.
[0017] When implementing the above embodiment, preferably, the control parameters of the extruder are that the temperatures of the feeding zone, reaction zone and extrusion zone are 170-200° C., 190-240° C. and 200-230° C. respectively, and the reaction time is 1-5 min.
[0018] When implementing the above embodiment, preferably, the weight ratio of the matrix, the melt enhancer with active functional groups and the catalyst is (80-100): (5-15): (2-5).
[0019] When implementing the above embodiment, preferably, the matrix is polylactic acid, polyhydroxyalkanoate or polybutylene succinate.
[0020] When implementing the above embodiment, preferably, the catalyst is one or more of a chromium catalyst, a metal carboxylate catalyst, a tin catalyst, hexamethylenetetramine or a quaternary ammonium salt catalyst.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The method for enhancing the melt strength of biodegradable plastics of the present invention comprises adding a melt enhancer with active functional groups, adopting a co-extrusion process of a base material and the melt enhancer with active functional groups, controlling the process conditions to use the melt enhancer with active functional groups in a reactive screw to perform a branching reaction on the molecules of the base material, thereby increasing the number of long chain branches of the base material and greatly improving the melt strength and thermoforming properties.
[0023] 2. The method for enhancing the melt strength of biodegradable plastics of the present invention adds a melt enhancer with active functional groups. The melt enhancer with active functional groups is applied to bio-based biodegradable plastics, can be well dispersed in the matrix material, and entangled with the molecules of the matrix material, thereby greatly improving the melt strength of the bio-based biodegradable plastics, better improving the processing performance of the bio-based biodegradable plastics, and improving the thermoformability of the bio-based plastics.
[0024] 3. The method for enhancing the melt strength of degradable plastics of the present invention adds a melt enhancer with active functional groups, and uses graphyne as a carrier. On the one hand, it can improve the dispersibility of the melt enhancer with active functional groups in the matrix material, so that it can fully react with the matrix material under the catalytic system; on the other hand, graphyne has a conjugated large π bond structure and a strong ability to capture free radicals, which can improve the thermal stability of the degradable plastic. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The reagents of the embodiments and comparative examples are described as follows:
[0027] Matrix: polylactic acid, Zhejiang Hisun Biotechnology;
[0028] Catalyst: Tetra-n-butylammonium chloride, Anhui Siyoupu Chemical;
[0029] Monomer with active functional group: maleic anhydride, Jinan Qicai Chemical;
[0030] Comonomer: methyl methacrylate, Shandong Runjin Chemical;
[0031] Graphene: Kramar.
[0032] It should be noted that, if no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used, and the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0033] Example 1
[0034] A method for enhancing the melt strength of a degradable plastic comprises the following steps:
[0035] Step 1: Add the monomer with active functional groups to acetone to prepare a solution with a concentration of 1 mol / L, add graphyne at a ratio of 1 g / L, stir for 15 min, and disperse in an ultrasonic disperser for 30 min to obtain a mixed liquid;
[0036] Step 2: irradiate the mixed liquid obtained in step 1 with γ-rays, with an irradiation dose of 50 kGy and an irradiation dose rate of 10 kGy / h, filter the sample obtained after irradiation, and repeatedly wash the filtrate, and then dry it in a vacuum oven at 60° C. to obtain graphene grafted with an active functional group monomer after drying;
[0037] Step 3: Add 1 part of the active functional group-grafted graphyne monomer obtained in step 2 and 15 parts of the copolymer monomer to 100 parts of a 1% by volume sodium dodecyl sulfate aqueous solution, mix and stir for 20 minutes, and pre-emulsify to obtain a pre-emulsified monomer;
[0038] Step 4: In a nitrogen atmosphere, 100 parts of a 1% sodium dodecyl sulfate aqueous solution were heated to 40° C. at a stirring speed of 100 r / min, and 100 parts of the pre-emulsified monomer obtained in step 3 were added dropwise to the sodium dodecyl sulfate aqueous solution for 2 hours. After the addition was completed, 0.01 parts of ammonium sulfate and 0.005 parts of sodium bisulfite were added in 3 batches, the reaction temperature was controlled at 40° C., and the reaction was carried out for 10 hours to obtain a polymer emulsion;
[0039] Step 5, drying the polymer emulsion to obtain a melt enhancer with active functional groups;
[0040] Step six, 80 parts of the matrix, 5 parts of the melt enhancer with active functional groups obtained in step five, and 2 parts of the catalyst are mixed and added to a twin-screw extruder, and the temperatures of the feeding zone, reaction zone, and extrusion zone of the twin-screw extruder are controlled to be 170-200°C, 190-240°C, and 200-230°C, respectively. The reaction time is 1 min, and the polylactic acid material is obtained by extrusion.
[0041] Example 2
[0042] A method for enhancing the melt strength of a degradable plastic comprises the following steps:
[0043] Step 1: Add the monomer with active functional groups to acetone to prepare a solution with a concentration of 2 mol / L, add graphyne at a ratio of 1.5 g / L, stir for 15 min, and disperse in an ultrasonic disperser for 30 min to obtain a mixed liquid;
[0044] Step 2, irradiating the mixed liquid obtained in step 1 with γ-rays, with an irradiation dose of 200 kGy and an irradiation dose rate of 100 kGy / h, filtering the sample obtained after irradiation, and repeatedly washing the filtrate, and drying it in a vacuum oven at 60° C. to obtain graphene grafted with an active functional group monomer after drying;
[0045] Step 3: Add 4 parts of the active functional group-grafted graphyne monomer obtained in step 2 and 20 parts of the copolymer monomer to 100 parts of a 1% by volume sodium dodecyl sulfate aqueous solution, mix and stir for 20 minutes, and pre-emulsify to obtain a pre-emulsified monomer;
[0046] Step 4: In a nitrogen atmosphere, 100 parts of a 1% sodium dodecyl sulfate aqueous solution were heated to 50° C. at a stirring speed of 180 r / min, and 100 parts of the pre-emulsified monomer obtained in step 3 were added dropwise to the sodium dodecyl sulfate aqueous solution for 3 hours. After the addition was completed, 0.01 parts of ammonium sulfate and 0.005 parts of sodium bisulfite were added in 3 batches, the reaction temperature was controlled at 50° C., and the reaction was carried out for 14 hours to obtain a polymer emulsion;
[0047] Step 5, drying the polymer emulsion to obtain a melt enhancer with active functional groups;
[0048] Step six, 88 parts of the matrix, 8 parts of the melt enhancer with active functional groups obtained in step five, and 3 parts of the catalyst are mixed and added to a twin-screw extruder, and the temperatures of the feeding zone, reaction zone, and extrusion zone of the twin-screw extruder are controlled to be 170-200°C, 190-240°C, and 200-230°C, respectively. The reaction time is 3 minutes, and the polylactic acid material is obtained by extrusion.
[0049] Example 3
[0050] A method for enhancing the melt strength of a degradable plastic comprises the following steps:
[0051] Step 1: Add the monomer with active functional groups to acetone to prepare a solution with a concentration of 4 mol / L, add graphyne at a ratio of 2.5 g / L, stir for 15 min, and disperse in an ultrasonic disperser for 30 min to obtain a mixed liquid;
[0052] Step 2: irradiating the mixed liquid obtained in step 1 with γ-rays, with an irradiation dose of 400 kGy and an irradiation dose rate of 150 kGy / h, filtering the sample obtained after irradiation, and repeatedly washing the filtrate, and drying it in a vacuum oven at 60° C. to obtain graphene grafted with an active functional group monomer after drying;
[0053] Step 3: Add 8 parts of the active functional group-grafted graphyne monomer obtained in step 2 and 25 parts of the copolymer monomer to 100 parts of a 1% by volume sodium dodecyl sulfate aqueous solution, mix and stir for 20 minutes, and pre-emulsify to obtain a pre-emulsified monomer;
[0054] Step 4: In a nitrogen atmosphere, 100 parts of a 1% sodium dodecyl sulfate aqueous solution were heated to 60° C. at a stirring speed of 250 r / min, and 100 parts of the pre-emulsified monomer obtained in step 3 were added dropwise to the sodium dodecyl sulfate aqueous solution for 5 hours. After the addition was completed, 0.5 parts of ammonium sulfate and 0.01 parts of sodium bisulfite were added in 3 batches, the reaction temperature was controlled at 60° C., and the reaction was carried out for 18 hours to obtain a polymer emulsion;
[0055] Step 5, drying the polymer emulsion to obtain a melt enhancer with active functional groups;
[0056] Step six, 100 parts of the matrix, 12 parts of the melt enhancer with active functional groups obtained in step five, and 5 parts of the catalyst are mixed and added to a twin-screw extruder, and the temperatures of the feeding zone, reaction zone, and extrusion zone of the twin-screw extruder are controlled to be 170-200°C, 190-240°C, and 200-230°C, respectively. The reaction time is 5 minutes, and the polylactic acid material is obtained by extrusion.
[0057] Example 4
[0058] A method for enhancing the melt strength of a degradable plastic comprises the following steps:
[0059] Step 1: Add the monomer with active functional groups to acetone to prepare a solution with a concentration of 5 mol / L, add graphyne at a ratio of 3 g / L, stir for 15 min, and disperse in an ultrasonic disperser for 30 min to obtain a mixed liquid;
[0060] Step 2, irradiating the mixed liquid obtained in step 1 with γ-rays, with an irradiation dose of 500 kGy and an irradiation dose rate of 200 kGy / h, filtering the sample obtained after irradiation, and repeatedly washing the filtrate, and drying it in a vacuum oven at 60° C. to obtain graphene grafted with an active functional group monomer after drying;
[0061] Step 3: Add 10 parts of the active functional group-grafted graphyne monomer obtained in step 2 and 30 parts of the copolymer monomer to 100 parts of a 1% by volume sodium dodecyl sulfate aqueous solution, mix and stir for 20 minutes, and pre-emulsify to obtain a pre-emulsified monomer;
[0062] Step 4: In a nitrogen atmosphere, 100 parts of a 1% sodium dodecyl sulfate aqueous solution were heated to 80° C. at a stirring speed of 300 r / min, and 100 parts of the pre-emulsified monomer obtained in step 3 were added dropwise to the sodium dodecyl sulfate aqueous solution for 6 hours. After the addition was completed, 0.5 parts of ammonium sulfate and 0.01 parts of sodium bisulfite were added in 3 batches, the reaction temperature was controlled at 80° C., and the reaction was carried out for 20 hours to obtain a polymer emulsion;
[0063] Step 5, drying the polymer emulsion to obtain a melt enhancer with active functional groups;
[0064] Step six, 100 parts of the matrix, 15 parts of the melt enhancer with active functional groups obtained in step five, and 5 parts of the catalyst are mixed and added to a twin-screw extruder, and the temperatures of the feeding zone, reaction zone, and extrusion zone of the twin-screw extruder are controlled to be 170-200°C, 190-240°C, and 200-230°C, respectively. The reaction time is 5 minutes, and the polylactic acid material is obtained by extrusion.
[0065] The polylactic acid particles obtained in Examples 1-4 and the blank group polylactic acid were dried in a vacuum oven at 80° C. for 12 hours, and then their melt strength (MS) was measured. The test results are shown in Table 1 below:
[0066] Table 1
[0067]
[0068] According to the test results in Table 1, the melt strength of polylactic acid in Examples 1-4 is significantly improved compared with that in the blank group, which proves that the method for enhancing the melt strength of degradable plastics of the present invention has a significant improvement in improving the melt strength of polylactic acid.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for enhancing the melt strength of a degradable plastic, characterized in that: The method comprises the following steps: mixing a matrix, a melt enhancer with an active functional group and a catalyst, adding the mixture into a twin-screw extruder, and performing reaction extrusion to obtain a degradable plastic; The melt enhancer with active functional groups is obtained by grafting monomers with active functional groups onto graphene and copolymerizing with comonomers; The monomer with active functional group is one or more of acrylic acid, maleic anhydride, methacrylic acid or glycidyl methacrylate; The comonomer is one or more of methyl methacrylate, butyl methacrylate or butyl acrylate; The preparation steps of the melt enhancer with active functional groups include: Step 1: preparing a monomer solution with an active functional group at a concentration of 1 to 5 mol / L, adding graphyne to the monomer solution with an active functional group at a ratio of 1 to 3 g / L, and stirring to obtain a mixed liquid; Step 2: irradiating the mixed liquid obtained in step 1 with γ-rays, and obtaining the grafted graphyne with active functional group monomer after drying; Step 3: adding the active functional group-grafted graphyne monomer obtained in step 2 and the comonomer to an aqueous solution of sodium dodecyl sulfate, mixing and stirring, and pre-emulsifying to obtain a pre-emulsified monomer; Step 4: heating the sodium dodecyl sulfate aqueous solution to 40°C-80°C at a stirring speed of 100-300 r / min, and dropping the pre-emulsified monomer obtained in step 3 into the sodium dodecyl sulfate aqueous solution for 2-6 hours. After the dropwise addition is completed, adding ammonium persulfate and sodium bisulfite in 3 batches, controlling the reaction temperature at 40°C-80°C, and reacting for 10-20 hours to obtain a polymer emulsion; Step 5: Drying the polymer emulsion to obtain a melt intensifier with active functional groups.
2. The method for enhancing the melt strength of degradable plastic according to claim 1, characterized in that: In step 2, the irradiation dose is 50 to 500 kGy, and the irradiation dose rate is 10 to 200 kGy / h.
3. The method for enhancing the melt strength of degradable plastic according to claim 1, characterized in that: The control parameters of the extruder are as follows: the temperatures of the feeding zone, the reaction zone and the extrusion zone are 170-200° C., 190-240° C. and 200-230° C. respectively, and the reaction time is 1-5 min.
4. The method for enhancing the melt strength of degradable plastic according to claim 1, characterized in that: The weight ratio of the matrix, the melt enhancer with active functional groups and the catalyst is (80-100): (5-15): (2-5).
5. The method for enhancing the melt strength of degradable plastic according to claim 1, characterized in that: The matrix is polylactic acid, polyhydroxyalkanoate or polybutylene succinate.
6. The method for enhancing the melt strength of degradable plastic according to claim 1, characterized in that: The catalyst is one or more of a chromium catalyst, a metal carboxylate catalyst, a tin catalyst, hexamethylenetetramine or a quaternary ammonium salt catalyst.
Citation Information
Patent Citations
Method for improving melt strength of polyester resin
CN103626982A